2022
DOI: 10.31557/apjcp.2022.23.5.1777
|View full text |Cite
|
Sign up to set email alerts
|

The Pathological Evaluation of Autophagy-Related Protein (LC3B) and Its Association with the Infiltration of Immune Cells in Glioma

Abstract: Background: Tumor cell autophagy can influence cellular immunity by participation in the recognition and modification of tumor-related antigens. Objectives: The objective of this study was to evaluate the immunohistochemical expression of the autophagy-related marker; light chain 3B (LC3B) in tumor cells and the assessment of T lymphocytes by a cluster of differentiation 3 (CD3) in gliomas, and to correlate them with the available clinic-pathological variables in glioma patients. Materials and methods: Immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
2
0
0
Order By: Relevance
“…Similarly, out of the 20 strongly positive cases of SQSTM1/p62 , none were found in the LGG category, and this difference achieved statistical significance (as indicated in Table 3 ). These results are in accordance with other studies, which reported that LC3B and SQSTM1/p62 were highly expressed in high-grade gliomas [ 29 , 30 , 31 ]. Remarkably, there is a statistically significant association between the autophagy markers LC3B and SQSTM1/p62 ( p = 0.000), highlighting the interaction between them.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, out of the 20 strongly positive cases of SQSTM1/p62 , none were found in the LGG category, and this difference achieved statistical significance (as indicated in Table 3 ). These results are in accordance with other studies, which reported that LC3B and SQSTM1/p62 were highly expressed in high-grade gliomas [ 29 , 30 , 31 ]. Remarkably, there is a statistically significant association between the autophagy markers LC3B and SQSTM1/p62 ( p = 0.000), highlighting the interaction between them.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, out of the 20 strongly positive cases of SQSTM1/p62, none was found in the LGG category, and this difference achieved statistical significance (as indicated in Table 3). These results were in accordance with other studies which reported that LC3B and SQSTM1/p62 was highly expressed in high grade gliomas [29][30][31]. Remarkably there is statistically significant association between the autophagy markers LC3B and SQSTM1/p62 (p=0.000), highlighting the interaction among each other.…”
Section: Discussionsupporting
confidence: 92%